DNS blocking in KW: tiktok.com, twitter.com (Kuwait) - Voidly (2026)
CRITICAL severity censorship detected in Kuwait. Confidence: 85%. Data sourced from CensoredPlanet.
Censorship Incident ID: KW-2026-0002
Keywords: censorship; KW; censorship; critical